BASELINE STUDIES ON RADIONUCLIDE CONCENTRATION IN FOOD MATERIALS AND ESTIMATION OF THE COMMITTED RADIATION DOSE AROUND THE PHOSPHATE INDUSTRIAL AREA OF SOUTH TUNISIA. Issue 2 (12th April 2018) - Machraoui, Sonia; Mohan, M P; Naregundi, Karunakara; Labidi, Salam
Abstract: The activity concentration of natural and anthropogenic radionuclides was determined in different vegetable samples, and foods derived from animal origin, from different locations in the four cities of Southern Tunisia, where large-scale phosphate industries are operating. The aim of the studies was to establish a baseline database on radionuclide concentration in food materials and to evaluate the radiation dose to the general population due to its ingestion through the food chain. The activity concentrations of 40 K, 210 Pb, 226 Ra, 228 Ra and 137 Cs was determined by gamma spectrometry using a HPGe detector, and from the measured activity concentrations, the doses were estimated using the dose coefficients given by the ICRP. The dose due to intake of radionuclides through mineral water was also determined. The total annual effective doses were found to be 2.2, 1.4, and 0.7 mSv y −1 for 1 y, 5–15 y and adult (>17 y) age groups, respectively. Among the radionuclides studied, 210 Po was the highest contributor to the total dose, followed by 210 Pb.